Assessment of an Extended Interval Fondaparinux Dosing Regimen for Venous Thromboembolism Prophylaxis in Critically Ill Patients with Severe Renal Dysfunction Using Antifactor Xa Levels. Issue 10 (18th October 2017) - Wahby, Krista A.; Riley, Lauren K.; Tennenberg, Steven D.
Abstract : Objective: Pharmacologic options for venous thromboembolism (VTE) prophylaxis are often limited in critically ill patients due to thrombocytopenia and multisystem organ dysfunction. Fondaparinux offers potential advantages in the critically ill; however, it is currently contraindicated in severe renal dysfunction (SRD). We evaluated anti–factor Xa levels in critically ill patients with SRD who were receiving an extended interval dosing regimen of fondaparinux for VTE prophylaxis. Methods: A prospective, single‐arm, interventional study was conducted at two academic hospitals of the Detroit Medical Center. Eligible patients were in the intensive care unit, had an estimated creatinine clearance of less than 30 ml/minute, and had either acute kidney injury or end‐stage renal disease; several patients were taking renal replacement therapy. Fondaparinux was administered at an extended interval dosing regimen of 2.5 mg subcutaneously every 48 hours. Fondaparinux peak and trough anti–factor Xa levels were obtained. Lower extremity venous duplex studies were performed at baseline and study completion to assess for deep vein thrombosis (DVT), and patients were monitored for bleeding complications. Results: Thirty‐two patients were enrolled. Patients received a median of four doses (interquartile range two to five) of fondaparinux. Fondaparinux peak (n=98) and trough (n=86) anti–factor Xa levels were 0.36 ± 0.18 mg/L and 0.17 ± 0.11 mg/L (mean ± SD), respectively, and were similar to levels reported in patients with normal renal function receiving conventional once‐daily dosing. No lower extremity DVTs or suspected VTE events occurred. Two (6%) patients had significant bleeding events. Conclusions: In critically ill patients with SRD, an extended interval fondaparinux dosing regimen of 2.5 mg every 48 hours for VTE prophylaxis achieved peak and trough anti–factor Xa levels similar to those reported in noncritically ill patients with normal renal function receiving once‐daily fondaparinux. This regimen offers an alternative for patients with SRD when heparinoids must be avoided.